2017
DOI: 10.1002/cncy.21900
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year cytohistological correlation of salivary gland FNA cytology at a tertiary center with the application of the Milan system for risk stratification

Abstract: Salivary gland FNA continues to have high diagnostic accuracy and is thus helpful for guiding management. Neoplasms with classic cytomorphology are easily diagnosed; however, in difficult cases showing overlapping features, the use of the Milan system could be beneficial. Cancer Cytopathol 2017;125:767-75. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

68
198
12
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(281 citation statements)
references
References 24 publications
68
198
12
3
Order By: Relevance
“…The ROM in the neoplastic group was found to be 12%, which is within the range seen in other studies (0-13%) and comparable to the NEG category ROM [12,18]. The ROM for SUMP in the available literature ranges from 0 to 100% [13]; in our study it was found to be 44%.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The ROM in the neoplastic group was found to be 12%, which is within the range seen in other studies (0-13%) and comparable to the NEG category ROM [12,18]. The ROM for SUMP in the available literature ranges from 0 to 100% [13]; in our study it was found to be 44%.…”
Section: Discussionsupporting
confidence: 74%
“…These cases turned out to be non-malignant on histological follow-up, resulting in a ROM of 0%, as was seen in the study by Thiryayi et al [19]. The ROM for the AUS category was 19% in the study by Layfield et al [20], while Rohilla et al [18] found a ROM of 100%.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The Milan System was introduced in 2017 for standardizing FNAC reports . Several studies have proven its efficacy and determined the risk of malignancies according to each category of the Milan System …”
Section: Discussionmentioning
confidence: 99%
“…Several studies focusing on the criteria outlined in the MSRSGC have already been initiated and published [28, 29]. These early studies have demonstrated the applicability of the MSRSGC in general cytology practice while also highlighting some issues that can be resolved with its implementation.…”
Section: What Were the Steps In The Development Of Msrsgc? The Histormentioning
confidence: 99%